2005
DOI: 10.1007/s11252-005-1421-6
|View full text |Cite
|
Sign up to set email alerts
|

Riparian woody plant diversity and forest structure along an urban-rural gradient

Abstract: Changes in riparian woody plant assemblages are anticipated in the southeastern United States due to increases in urbanization rates. Because riparian forests serve important roles in maintaining water quality and biodiversity, understanding how they respond to urbanization is crucial. The objective of this study was to examine forest structure and woody vegetation diversity indices of riparian communities in response to an urbanization gradient in West Georgia, USA. Measures of forest structure and diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 37 publications
8
88
1
10
Order By: Relevance
“…These differences express the variable environmental conditions in the adjacent segments of the moisture gradient. Burton et al (2005) found significant decrease in basal area and forest cover along the urban gradient. They ascribed this phenomenon to decreasing forest productivity and history of timber harvesting.…”
Section: Environmental and Disturbance Gradientsmentioning
confidence: 87%
See 1 more Smart Citation
“…These differences express the variable environmental conditions in the adjacent segments of the moisture gradient. Burton et al (2005) found significant decrease in basal area and forest cover along the urban gradient. They ascribed this phenomenon to decreasing forest productivity and history of timber harvesting.…”
Section: Environmental and Disturbance Gradientsmentioning
confidence: 87%
“…Burton et al (2005) reported that the proportion of non-native species in the canopy and regeneration layer decreased and diversity of the regeneration layer increased along an urban gradient of the riparian forest studied. They assigned this pattern to the anthropogenic disturbance that may subdue the ability of diverse communities to resist non-native plant invasions.…”
Section: Diversitymentioning
confidence: 94%
“…Model selection was made by comparing all candidate models using Akaike's Information Criteria (Burnham and Anderson 2003) by developing a series of alternative mixed effect models that include different combinations of the explanatory variables (Zuur et al 2009 , Table 1), by fitting the full model with the set of all possible explanatory variables and taking out the least significant term on each step (Crawley 2007). We then ranked the models according to AIC differences (Δ i = AIC i -AIC min , where AIC i is the model i value and AIC min is the best model value).…”
Section: Discussionmentioning
confidence: 99%
“…Models with Δ i < 2 provide substantial support for a candidate model, whereas values of Δ i between 4 and 7 provide less support and Δ i > 10 indicates that the model is unlikely. We also calculated Akaike weights for all models, where these model weights are used to indicate the importance of a model, with increasing weights indicating the likelihood of a particular model as the overall best model (Burnham and Anderson 2003). Aikaike weights can also be used to calculate the relative importance of a variable by summing the Akaike weights of all models that include that variable (Burnham and Anderson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Most trees ranged between 2.5-and 25-cm in diameter at breast height (DBH) ( Table 2- Species richness of woody vegetation can differ dramatically along an urban-torural gradient (Burton et al 2005, Burton andSamuelson 2008). As such, species richness for woody plant communities was computed as one measure of species diversity and was computed individually for trees, saplings, tree seedlings, and shrubs.…”
Section: Plant Communities In Relation To Land-covermentioning
confidence: 99%